Postcard from Georg Bredig to Max Bredig, September 3, 1936 - Bredig, Georg (1936)
Georg Bredig (1868-1944) asks his son, Max Albert Bredig (1902-1977) how he is because he has not written to him. Georg tells him that Marianne Homburger (1903-1986) and Mrs. Lot are helping him clean his apartment.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986